Sistem Informasi Manajemen Pelayanan Pendaftaran Tes Minnesota Multiphasic Personality Inventory (MMPI) Di RSJ Provinsi Babel - Embun Ventani; Riki Afriansyah; Yang Agita Rindri; Yuliyanto Yuliyanto (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
Mental health is important because mentality greatly influences a person's quality of life. The mental hospital is the only government agency that provides MMPI test services in Bangka Belitung. The MMPI is a self-report inventory of 550 true/false items that have historically been used to assess test takers' personalities, as well as their personal and social adjustments. The obstacle faced at this RSJ is that it still uses a manual registration system to carry out registration services for participants who take the MMPI test. Automatically this causes an accumulation of registrants who want to register, especially since the registration system used still uses paper forms. Based on these problems, an information system is needed to facilitate registration and data collection. The method used is the prototype method which consists of the stages of gathering requirements, building prototypes, evaluating, coding and testing. System design is carried out using the Unified Modeling Language (UML) method which consists of Use Cases, Entity Relationship Diagrams, and Activity diagrams. System testing is carried out using the UAT BlackBox Testing method and the Technology Acceptance Model (TAM). The results of the BlackBox test show that 100% of the system works perfectly, while the TAM test shows that 88.22% of respondents feel the system is easy to use and not complicated, 85.33% of respondents have an interest in using the system, and 88.33% of respondents feel the system provides benefits and has used for the registration process.